Tinjauan Ulang Potensi Sense of place dalam Pelestarian Kawasan Pusaka Perkotaan - Christin Dameria; Roos Akbar; Petrus Natalivan Indradjati; Dewi Sawitri Tjokropandojo (Diponegoro University, 2020)
Urban heritage conservation planning seeks to produce place experience with historical characteristics to bring sense of place that is a relation between human and place. However heritage urban planning that focuses on the sense of place actually gets criticized for being stuck in place-making purposes only and ignores the human dimension. The study of the sense of place potential in the urban heritage conservation is indeed still limited even though this potential needs to be studied futher because urban heritage place have cultural significant values which should be conserved by involving human dimensions. This paper is a literature review that intends to explore others sense of place potential related to human dimensions that can be used to successfully urban heritage conservation. In urban heritage conservation, besides being beneficial for place-making, it was found that the sense of place also has the potential as guidance information in the urban heritage spatial planning, factors that influence the participation of local residents to be involved in urban heritage planning and factors related to heritage conserving behavior.